PENGARUH ASIMETRI INFORMASI, FINANCIAL DISTRESS, TINGKAT PENDIDIKAN DEWAN DIREKSI, KEBERAGAMAN GENDER DEWAN DIREKSI TERHADAP MANAJEMEN LABA - Megawati, Yuliana; Sulfitri, Virna (LPPM Universitas Ibnu Sina, 2023)
Empirical evidence on the effect on firm value of financial distress, board diversity, and information asymmetry in good corporate governance mechanisms in which gender diversity and educational level of the board of directors act as proxies. The samples of this research data are annual reports and financial reports owned by companies listed on the Indonesia Stock Exchange (IDX) in 2019 to 2021, especially BUMN. There are 15 companies that match the criteria so that there are 45 sample data used in the study by selecting using purposive sampling. In testing the impact of earnings management on financial distress, the education level of the board of directors, information asymmetry, and gender diversity of the board of directors. From the results of this study it was found that there was a positive influence on earnings management from financial distress and information symmetry while there was a negative effect from the level of education and gender diversity of the board of directors.